The attic : memoir of a Chinese landlord's son - Cao, Guanlong, 1945- (University of California Press, 1996)
In this exquisite memoir, novelist Guanlong Cao sketches the tales of growing up in Shanghai during the tumultuous Cultural Revolution. Forced to the bottom of the Chinese society as "class enemies" because Cao's father was a petty landlord, his family eked out a meager existence in a cramped attic in a tiny corner of Shanghai. Through the eyes of a child growing into a young man, we observe the tenderness, the tragedy, and even the humor of daily life: the endless quest for enough food, children's games and fantasies, sexual stirrings, exile to the countryside, imprisonment, sickness, old age, and death. Political upheavals flicker across the background, occasionally intruding into the lives of this ordinary - and yet utterly extraordinary - family. Reminiscent of the concise style of classical Chinese memoirs, Cao's lean, elegant prose heightens the emotional intensity of his story. Perceptive and humorous, his voice is deeply original. It is a voice that demands to be heard - for the historical moment it captures as well as for the personal revelations it distills